Prosperity Gospels and Money Worship in Nigeria: Exploring Miracles for Poverty Alleviation - Amobi P. Chiamogu; Uchechukwu P. Chiamogu; Anthony-Mary Chukwudozie Amali (Jurnal Mengkaji Indonesia, 2026)
Abstract: The prosperity gospel, which promises material wealth and success as evidence of divine favour, has gained widespread popularity, especially among those facing economic hardship in Nigeria. This doctrine, propagated by influential religious leaders, encourages the belief that faith, positive confession and financial contributions to the church can lead to miraculous financial breakthroughs. Purpose: This study examined the phenomenon of prosperity gospels and money worship in Nigeria, probing how these religious practices are perceived as mechanisms for poverty alleviation. Design/Methodology/Approach: The study adopted an explanatory research design and utilized the documentary method to collect data from secondary sources, while a textual analysis rooted in systematic logical induction was employed to test the hypotheses. Findings: The study critically analyzed the socio-economic context that has given rise to this religious movement, emphasizing how poverty and economic instability have made the promises of prosperity gospels appealing to a large segment of the population. However, it also revealed the controversies surrounding this practice, including accusations of exploitation, materialism and the commercialization of religion. The research is grounded in Max Weber’s theory of religion and capitalism, Marxist theory of religion, social exchange theory and spiritual capital theory to explore how prosperity gospels shape economic behaviour and perpetuate social inequality. While prosperity gospels may offer temporary hope and psychological relief, they often fail to address the structural causes of poverty in Nigeria, potentially exacerbating economic disparities and diverting attention from sustainable solutions. Originality/value: The study contributed to the ongoing discourse on the connection of religion, economics and social justice in Nigeria, offering insights into the intricate role of religious practices in addressing or perpetuating poverty.